Relaxation mechanisms in ultra-low damping Fe80Co20 thin films - Velázquez Rodriguez, Daniel (2020)
Ferromagnetic thin films with ultra-low damping constants (α) are intensively studied for applications in spintronic devices. We report here the influence of the sputtering conditions (deposition power and temperature) on the magnetic properties of Fe80Co20/Ta bilayers deposited on MgO (0 0 1) and Si (0 0 1) which have been studied using ferromagnetic resonance (FMR) and magneto-optic Kerr-effect (MOKE) techniques. We have found that for the studied fabrication conditions the samples deposited on MgO (0 0 1) have [1 0 0] epitaxial growth with a cubic anisotropy field Hc ~ 300 Oe, while those sputtered on Si (0 0 1) grow polycrystalline with a small uniaxial anisotropy due to the deposition conditions. With measurements at different excitation frequencies we have determined exceptionally low damping values for ferromagnetic conductors (α ~ 3 × 10−3), which makes the Fe80Co20/Ta system an excellent candidate for future applications in spintronic devices. From the analysis of the dependence of the FMR linewidth on the orientation of the applied magnetic field and the excitation frequency in FMR experiments, we were able to separate the contribution of the different relaxation mechanisms (Gilbert damping, two magnon scattering and mosaicity) to the linewidth and to explain quantitatively the observed behavior.